A juvenile Koskinonodon perfectus (Temnospondyli, Metoposauridae) from the Upper Triassic of Arizona and its implications for the taxonomy of North American metoposaurids. (2nd May 2017) - Gee, Bryan M.; Parker, William G.
Abstract: Metoposaurids are temnospondyl amphibians that are well known from Upper Triassic deposits in North America, Europe, India, and Africa. Two species of metoposaurids, Koskinonodon perfectus and Apachesaurus gregorii, are among the most common fossils found in the Petrified Forest National Park (PEFO) of the southwestern United States. The two are distinguished on the basis of several cranial traits and the morphology of their intercentra, and are more informally distinguished by their overall size and biostratigraphic range. While material of adult metoposaurids is extremely common in Upper Triassic deposits, described material of juveniles is very rare, which limits the study of ontogenetic trajectories that would assist in assessing whether diagnostic traits of the smaller A . gregorii are also ontogenetically influenced traits in juveniles of K . perfectus . Here we report on material from a juvenile specimen of K . perfectus from the Petrified Forest Member (Norian) of the Chinle Formation in the PEFO. This specimen is significant because it represents the highest known occurrence of the species within the PEFO, documents a rare occurrence of a juvenile specimen of a North American metoposaurid, and records a rare North American metoposaurid specimen that includes associated cranial and postcranial material. Additionally, the combination of cranial features diagnostic of K . perfectus and intercentra of proportions intermediate between K . perfectus and A . gregorii in this specimen raises questions about the utility of several characters for species discrimination in North American metoposaurids.